Strategi Mesir Menghadapi Ancaman Pembangunan Grand Ethiopian Renaissance Dam (Gerd) - Meitha Tristiani Gea; Rahmawati, Asterina (Department of International Relations, Brawijaya University, 2022)
ABSTRACT Nile river passes through Egypt, Tanzania, the Democratic Republic of the Congo, Ethiopia, Uganda, Kenya, Sudan, Rwanda, Eritrea and southern Sudan. The river that is the pride of the Egyptian state does flow to various countries, but other countries do not feel the benefits at all. Only Egypt has the right to use the water of the Nile in accordance with the treaties in 1929 and 1959. 97% of Egypt's water supply comes from the Nile. Egypt has become a country with strong control over the distribution of water discharge in the Nile. However, as a country mired in poverty and struggling with severe drought, Ethiopia, considers the agreement irrelevant and very detrimental. Ethiopia finally challenged the historical water access rights through the construction of the Grand Ethiopian Renaissance Dam (GERD). This project is planned to be completed in 2022. However, the construction of this dam by Ethiopia of course be a big threat to Egypt because it can drastically reduce the availability of water to the country, so the right strategy is needed to be able to overcome the threat of GERD development. The paper in this study aims to find out how Egypt's strategy is in dealing with the threat of the construction of the Grand Ethiopian Renaissance Dam (GERD). In this study, the author applies a qualitative method. The author utilizes various related sources such as journals and books and is analyzed using the theory of the National Interest to be able to answer research questions Keywords: Egypt, Ethiopia, GERD, Nile River